2017
DOI: 10.1111/1471-0307.12484
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterisation of a sugar‐free milk‐based dessert formulation with fig (Ficus carica L.) and carboxymethylcellulose

Abstract: The objective of this study was to develop an optimum formula for ‘Shir Anjir’, an Iranian dessert containing milk, dried fig (13, 16.5, 20%) and carboxymethylcellulose (CMC) (0, 0.35, 0.7%) with no added sugar. Apparent viscosity, flow behaviour indices, pH, acidity (% lactic acid), total solid and colour parameters were compared. Sensory tests were performed to evaluate degree of liking of colour, appearance, taste, texture, mouthfeel and general acceptance. Figs and CMC influenced the dessert's characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Currently, the food market forces the industries concerned to formulate new products that meet the requirements of the consumer, from the functional properties, nutritional, and therapeutic point of view. Recent studies have been conducted dealing with the effect of alternative sweeteners to sucrose on rheological behavior, sensory and physicochemical properties, and identifying several beneficial attributes of dairy desserts (Gurditta, Patel, & Arora, ; Jahromi & Niakousari, ; Prasad, Khamrui, Mandal, & Badola, ). However, the available studies only evaluate the impact of this substitution on the characteristics of the products.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the food market forces the industries concerned to formulate new products that meet the requirements of the consumer, from the functional properties, nutritional, and therapeutic point of view. Recent studies have been conducted dealing with the effect of alternative sweeteners to sucrose on rheological behavior, sensory and physicochemical properties, and identifying several beneficial attributes of dairy desserts (Gurditta, Patel, & Arora, ; Jahromi & Niakousari, ; Prasad, Khamrui, Mandal, & Badola, ). However, the available studies only evaluate the impact of this substitution on the characteristics of the products.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the proposed plant ingredients on the physical-chemical parameters of dairy products has been studied in [3,6,14,20]. But the microbiological parameters of dairy products during storage have not been studied, which is an important aspect in substantiating the shelf life.…”
Section: Discussion Of Results Regarding the Quality Indicators Of Sour Milk Dessertmentioning
confidence: 99%
“…There is the dessert containing milk, dried figs, and carboxymethylcellulose [14]. But the cited work did not study the microbiological characteristics of dessert, which affect the quality and safety of the finished product.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The authors also reported how the addition of fig seed powder to the formulation of a cookie improved its fiber content and also increased the total phenolic content and antioxidant activity [39]. Additionally, fig by-products' sweet extracts have been used for making traditional desserts without adding sugar, for example "Shir Anjir", an Iranian dessert [40]. Minimally processed fruits, such as smoothies, retain a large number of phytochemicals and they could in fact be considered a valid alternative to eating fresh fruits.…”
Section: Bioactive Content Of Fig-based Products and Their Antioxidant Activitymentioning
confidence: 99%